Cure characteristics of unaccelerated sulfur vulcanization of epoxidised natural rubber - Poh B T; Chen M F; Ding B S (Journal of Applied Polymer Science, 1996)
The curing characteristics of unaccelerated sulfur vulcanization of ENR 25 and ENR 50 were studied in the temperature range from 100-180 C. The range of sulfur loadings was from 1.5 to 6.5phr. The scorch time was determined by Mooney Shearing Disk Viscometer whereas the initial cure rate, maximum torque and reversion properties were obtained from the Moving Die Rheometer (MDR 2000). Results shows that ENR 25 gives a longer scorch time than ENR 50, an observation similar to that in an accelerated system reported earlier. For temperature <120 C, scorch time depends exponentially on sulfur loading for both rubbers. However, this dependence diminishes as temperature is increased. This observation is attributed to the availability of activated sulfur molecules for vulcanization. The initial cure rate and maximum torque increases with increasing sulfur loading. ENR 50, however, exhibits higher value than ENR 25, suggesting faster cure in the former. For a fixed sulfur loading, reversion is a time and temperature-dependent phenomenon. It decreases with increasing sulfur loading because of the increase of cross-linking density for both rubbers studied.
Keywords: Epoxidized natural rubber; Sulfur vulcanization